2002
DOI: 10.1002/tox.10047
|View full text |Cite
|
Sign up to set email alerts
|

Immunocompetence of bivalve hemocytes as evaluated by a miniaturized phagocytosis assay

Abstract: Immune function in bivalves can be adversely affected by long-term exposure to environmental contaminants. Investigating alterations in immunity can therefore yield relevant information about the relationship between exposure to environmental contaminants and susceptibility to infectious diseases. We have developed a rapid, cost-effective, and miniaturized immunocompetence assay to evaluate the phagocytic activity, viability, and concentration of hemocytes in freshwater and marine bivalves. Preliminary experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
1
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(24 citation statements)
references
References 19 publications
(18 reference statements)
1
21
1
1
Order By: Relevance
“…Hemocytes of bivalves exposed for 62 days in cages at sites located downstream of the effluent plume in the SLR displayed a significant decrease in immunocompetence in relation to the upstream site (Blaise et al 2002), corroborating the 96-h laboratory exposure.…”
Section: Ecotoxicological Effects Of Effluents Laboratory Bioassayssupporting
confidence: 67%
“…Hemocytes of bivalves exposed for 62 days in cages at sites located downstream of the effluent plume in the SLR displayed a significant decrease in immunocompetence in relation to the upstream site (Blaise et al 2002), corroborating the 96-h laboratory exposure.…”
Section: Ecotoxicological Effects Of Effluents Laboratory Bioassayssupporting
confidence: 67%
“…45 By measuring the responses of a microplatebased phagocytosis assay appraising the capacity of mussel hemocytes to ingest fluorescent bacteria, results showed that phagocytosis activity was significantly suppressed in hemocytes after the 96 h-exposure to high concentrations (≥25% v/v) of the WWTP effluent, as well as after the two month caging experiment for mussels exposed downstream of the WWTP emission. 34 Similarly, phagocytosis measurements generated with endemic Mya arenaria soft-shell clams collected from intertidal zones of the Saguenay Fjord, a major affluent of the SLR estuary (Figure 2), also displayed immunosuppression in animals located in zones impacted by urban effluents. 46 Immunosuppression in hemocytes has also been observed in other urban effluents to which caged bivalves were exposed.…”
Section: Under a Slap-funded Urban Effluentmentioning
confidence: 87%
“…For example, WOE studies can include toxicity testing on whole organisms, multiple biomarker measurements, and chemistry on water, sediment and tissue, as well as ecological parameters. 25 With continuing development in ecotoxicological research that led to increasing numbers of biomarkers, they have often been grouped into different categories based on the type of ecotoxicity information that they engender (Table 1) 21,[26][27][28][29][30][31][32][33][34][35][36][37][38][39] . Of notable interest are biomarkers that can intimate exposure to a specific class of chemicals.…”
Section: Biomarkersmentioning
confidence: 99%
“…La phagocytose, entre autres, constitue un important moyen par lequel les hémocytes -cellules de l'hémolymphe composées de granulocytes et de hyalinocytes -peuvent gérer la prise en charge et l'élimination de microorganismes indésirables (GLINSKI et JAROSZ, 1997). Lors de la campagne de juin 1997, nous avons documenté l'immunocompétence de myes récoltés à plusieurs sites du fjord à l'aide d'une technique développée en microplaque qui mesure la capacité des hémocytes à phagocyter des bactéries fluorescentes (BLAISE et al, 2002b). Ce biomarqueur d'immunocompétence nous a signalé, comparativement aux sites de références ASE et BMB, une augmentation significative de l'activité de phagocytose aux sites AE, BE et ASJ, au sujet desquels des effets indésirables chez la mye ont déjà été observés précédemment, et qui se trouvent à plus grande proximité des sources industrielles et urbaines provenant de l'amont ( Figure 1).…”
Section: Immunocompétenceunclassified